Proposição de um modelo para diagnosticar o nível de maturidade de uma oferta de product-service system em um contexto B2B - Battaglia, Daniel (Universidade do Vale do Rio dos Sinos, 2017)
The concept of product-service systems (PSS) can be characterized as the extension of the operation of a physical good, adding specialized services that allow the promotion of the services offered. In this sense, the context of relationships businessto- business (B2B) brings together companies that buy goods and services to be used in the production/sale of goods and services to be offered to the customers. These interactions expand the perspective of relationships, adding long-term partnerships. Thus, this work aims to structure a model for diagnose the maturity level of a PSS offering by supplier companies that operate in a B2B context. The research method used is the exploratory multiple case study with qualitative approach. The sample selected consists of ten cases that offer solutions through PSS; five manufacturingoriented companies and five services-oriented companies. As a result, the model was able to diagnose the maturity levels of the companies investigated and reported for application in different contexts of business. As academic contributions, the model moves forward in order to structure a conceptual basis that adds a greater number of criteria to be considered for the provision of PSS, which still is not observed in the literature. Also, it collaborates for making combined use of qualitative information and categorical scale to compose the maturity diagnostics. In addition, allows the identification of the profile of organizations in relation to PSS practices adopted. As a managerial contributions, backed the model identification of potential inhibitors to be developed to offer PSS by the supplier companies, identifying managerial priorities and important strategies to be adopted and, also, contributes for the identification of opportunities to improve the PSS offerings.
Keywords: Modelo de maturidade; Relacionamento B2B; Critérios de PSS; Melhoria; Product-service system; Maturity model; B2B relationship; PSS criteria; Improvement.; ACCNPQ::Engenharias::Engenharia de Produção